Updated peer review of the pesticide risk assessment of the active substance pelargonic acid (nonanoic acid) - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal, 2025)
Abstract The conclusions of EFSA following the peer review of the initial risk assessments carried out by the competent authorities of the rapporteur Member State Greece and co‐rapporteur Member State Austria for the pesticide active substance pelargonic acid (nonanoic acid) and the considerations as regards the inclusion of the substance in Annex IV of Regulation (EC) No 396/2005 are reported. The context of the peer review was that required by Commission Implementing Regulation (EU) No 844/2012, as amended by Commission Implementing Regulation (EU) No 2018/1659. The conclusions were reached on the basis of the evaluation of the representative use of pelargonic acid as a herbicide on vineyards, potatoes, paths and places with woody plants, ornamental shrubs, ornamentals lawn, home gardens and allotments, paths and open areas with tree growth, woody ornamentals, decorative lawns, turf (field use). The conclusions reached in the renewal process were updated following the request from the European Commission via a specific mandate in accordance with Article 31 of Regulation (EC) No 178/2002, in conjunction with Regulation (EC) No 1107/2009, to further elaborate on certain aspects of the risk assessment for non‐target arthropods for the representative home and garden uses of the plant protection product ‘MON 74134’. The reliable end points, appropriate for use in regulatory risk assessment are presented. Missing information identified as being required by the regulatory framework is listed.